BARRIERS OF GREEN SUPPLY CHAIN MANAGEMENT IMPLEMENTATION IN MALAYSIAN CONSTRUCTION INDUSTRY - Wong, Shi Yee; Wah, Low Wai; Wong, Amos Sheng Min (Journal of Surveying, Construction and Property, 2023)
Profit maximization is a key priority of construction industry stakeholders but may challenge the stakeholders to look into other aspects. Environmental aspect is one of the sustainability elements that tends to be neglected in the supply chain management. Its impact on project site and living surrounding environment is either taken lightly or ignored by the construction stakeholders. This paper aims to investigate the barriers of the uptake of Green Supply Chain Management (GSCM) during the pre-construction stage of construction project to assist stakeholders with planning in relation to the environmental protection at the earliest stage of a project. Pre-construction is the stage within a project life cycle for decision making on the selection of materials, labours, plants and equipment. Questionnaire survey was distributed to the construction stakeholders, with 44 valid responses returned. The analysis was drawn from the feedback of the architects, contractors, consultants, and engineers. The results revealed that the critical barriers for the GSCM were lack of company’s leadership and support, lack of awareness, and lack of sustainable GSCM practices. This research provides an overview of current GSCM practices in Malaysia and alerts stakeholders to focus on specific organizational strategies in adopting GSCM.